(untitled) - Seiroku, Noma (Tokyo, Japan, 1967)
Art is the proof of the existence of spiritual values, and speaks an international language. This book is an attempt to explain the traditions which have shaped the art of Japan.
Keywords: Art, Japanese,Mỹ thuật, Nhật Bản